(3CLhHI eSGFds - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdeSCdI GdChdi McGjJgG GdYdI GdChdi deG aGQbJ GdYdd GdLhGH YfgG gPG GdSDGd jage Ydi hLgjf CMOgeG Cf GdeHOC GdChd gd gh eaGQb dZjQ HeaGQbI eYbhdI Ch gh eaGQb dPGJg s
(3BNQgG (B:s
(3aGdeYGdL GHJOGDg ef GdfaS hGdeJYGdL GHJOGDg ef GdHOf hGdaYd ef GdaGYd hGddg Gdehab ddNjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs